PENGARUH ADSORBEN TERHADAP AKTIVITAS ANTIOKSIDAN DARI ASAP CAIR KAYU CEMPAKA (Michelia champaka Linn) - Katja, Dewa Gede; Suryanto, Edi; Momuat, Lidya I.; Tambunan, Yenny (Sam Ratulangi University, 2008)
The objective of this study was to determine the effects of adsorbent on antioxidant activity of liquid smoke from champaka wood. The adsorbent was used as active carbon, silica gel and alumina. Concentration of adsorbent were added to liquid smoke fro 1-5%. Antioxidant activity of liquid smoke was evaluated in 1.1-diphenyl-2-picrylhydrazyl (DDPH) radical test. The liquid smoke was treated with third adsorbent in agitation for 15, 30 and 45 minutes. The effect of active carbon showed the highest scavenging activity in DPPH radical followed alumina and silica gel. This result showed that active carbon effect at concentration of 3 and 5% had highest antioxidant activity than alumina and silica gel for 45 and 60 minutes. This research concluded that active carbon could be increase antioxidant activity of liquid smoke.